Clustering of Crime-Prone Areas in East Medan Based on Police Data Using K-Means and DBSCAN Algorithms - Gaizka Pasya Dermawan Sinukaban; Al-Khowarizmi Al-Khowarizmi (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2026)
The Medan Timur sub-district is one of the high-crime areas in Medan City, recording 853 cases out of 1,308 criminal incidents collected by the Medan Timur Police Sector during the 2023–2025 period. The cases consist of motorcycle theft or curanmor (689 cases, 52.7%), aggravated theft or curat (448 cases, 34.3%), and robbery or curas (171 cases, 13.1%), spread across 20 sub-villages with a range of 13 to 162 cases per sub-village. This study clusters crime-prone areas using K-Means and DBSCAN algorithms and compares their performance through the Silhouette Index (SI) and Davies-Bouldin Index (DBI). The features used include total_kriminal, curanmor, curas, curat, and rata_waktu, normalized using Min-Max Normalization. The optimal number of clusters for K-Means was determined through the Elbow method yielding K=3, while DBSCAN parameters were determined through a KNN Distance Plot yielding eps=0.20 and minPts=2. Evaluation results show that K-Means yields SI=0.4105 (weak category) and DBI=1.2599, while DBSCAN yields SI=0.6788 (moderate category) and DBI=0.4986 on 8 non-noise sub-villages. DBSCAN outperforms K-Means on both metrics with an SI difference of 0.2683 and a DBI difference of 0.7613, although K-Means is superior in coverage by clustering all 20 sub-villages. These findings can be utilized by the Medan Timur Police Sector as a basis for determining priority patrol areas and allocating security resources more effectively. Keywords: Crime; Clustering; K-Means; DBSCAN; Silhouette Index; Davies-Bouldin Index